Social Entrepreneurship Intention: Part and Parcel of Intention-Based Theories and Models - Mohd Wahid, Siti Daleela; Wan Hussain, Wan Mohd Hirwani; Ayob, Abu Hanifah (Information Management and Business Review, 2024)
Investigating spending behavior among students is essential, particularly in understanding how they allocate funds toward academic priorities. This article aims to explore students’ spending habits and the key practices that influence the allocation of semester-based educational funding. The study adopts a quantitative, cross-sectional approach, with 501 respondents selected from six higher education institutions in Melaka through a quota sampling technique. Data analysis was conducted using IBM SPSS software (version 28.0). The results indicate that both financial management knowledge and peer influence have a positive impact on students’ spending behavior. This research contributes to the literature by enhancing the understanding of spending behavior patterns across the institutions studied, while also offering practical insights for higher learning institutions (HLIs) in Malaysia and their students. Limitations and suggestions for future research are also addressed.